An exploratory study of some of the determinants of managements succession planning in family businesses - Ellis, Susanna M.; Van der Merwe, Stephan; Venter, Elmarie (Southern African Institute for Management Scientists, 2009)
This study highlights the importance of management succession planning in small and medium-sized family businesses. The primary objective of this study is twofold : firstly to identify the potential influence of selected variables (determinants) on the management succession planning process in small and medium-sized family businesses, and secondly to make practical recommendations for actions that families can take to improve their chances of a successful succession and thereby ensure the sustainability of the family business for future generations. Structured questionnaires were received from 270 active family members from 77 family businesses. The data collected were subjected to various statistical analyses. An Oblimin oblique rotation was performed on the principal components of the exploratory factor analysis. In this study three factors describing the theoretical dimensions of management succession planning, perceived suitability of the prospective successor and the expected outcome of the succession were extracted. Based on the results of the regression analysis, both management succession planning and the perceived suitability of the prospective successor have a positive influence on the expected outcome of the succession. Although statistical significant differences were found between the perceptions of male and female as well as between senior- and younger-generation family employees regarding the variables, these differences were not practically significant. This study, however, confirms the important role that an effective management succession planning process plays in ensuring the successful transfer of the family business from the senior-generation owner-manager to the younger-generation family.